Chemical composition of the small mammal reproductive system as an indicator of enterprise technogenic impact on the environment; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Baranovskaya N. V. Nataliya Vladimirovna; Belyanovskaya A. I. Alexandra Igorevna; Bezel V.; Mukhacheva S.; Anufrieva M. A. Marina Aleksandrovna (Geoecology and Environmental Protection, 2016)
Title screen